A single centre retrospective study of low dose prophylaxis with extended half‐life factor IX for severe haemophilia B. Issue 2 (21st February 2020) - Rampotas, Alexandros; Desborough, Michael J. R.; Raza‐Burton, Sayma; Taylor, Stephanie; Wilkinson, Alice; Hall, Georgina W; Shapiro, Susan; Curry, Nicola
Abstract: Introduction: Extended half‐life factor IX concentrates (EHL‐FIX) can be administered weekly to prevent bleeding for persons with severe haemophilia B. We report the experience of a large UK haemophilia comprehensive care centre using low dose EHL‐FIX for persons with severe haemophilia B. Aim: The low doses used in real world are approximately half of the doses used in clinical trials. We aim to assess the efficacy and safety of low dose EHL‐FIX. Methods: Data from a cohort of 13 patients who were switched from standard half‐life factor IX (SHL‐FIX) to Alprolix ® (mean dose 31.5 IU/kg) and seven patients who switched from standard half‐life factor IX to Idelvion ® (mean dose 20.2 IU/kg) were included. Results: The median annualized bleeding rate was similar for SHL‐FIX (median 3, interquartile range [IQR] 1‐5) and EHL‐FIX (median 3, IQR 1‐5.25). Quality of life scores, measured using the European Quality of Life 5 Dimensions assessment were similar for SHL‐FIX (median 0.76, IQR: 0.63‐0.84) and EHL‐FIX (median 0.79, IQR: 0.58‐0.88). Conclusion: This study shows that EHL‐FIX given at low doses can be effective for prevention of bleeding for persons with severe haemophilia B.